Analysis of site-specific glycan profiles of serum proteins in patients with multiple sclerosis or neuromyelitis optica spectrum disorder—a pilot study. (14th June 2021) - Ip, Peng Peng; Li, Qiongyu; Lin, Wei-Han; Chang, Chien-Ching; Fann, Cathy Shen-Jang; Chen, Huan-Yuan; Liu, Fu-Tong; Lebrilla, Carlito B; Yang, Chih-Chao; Liao, Fang
Abstract: Glycosylation is important for biological functions of proteins and greatly affected by diseases. Exploring the glycosylation profile of the protein-specific glycosylation and/or the site-specific glycosylation may help understand disease etiology, differentiate diseases and ultimately develop therapeutics. Patients with multiple sclerosis (MS) and patients with neuromyelitis optica spectrum disorder (NMOSD) are sometimes difficult to differentiate due to the similarity in their clinical symptoms. The disease-related glycosylation profiles of MS and NMOSD have not yet been well studied. Here, we analyzed site-specific glycan profiles of serum proteins of these patients by using a recently developed mass spectrometry technique. A total of 286 glycopeptides from 49 serum glycoproteins were quantified and compared between healthy controls ( n  = 6), remitting MS ( n  = 45) and remitting NMOSD ( n  = 23) patients. Significant differences in the levels of site-specific N -glycans on inflammation-associated components [IgM, IgG1, IgG2, complement components 8b (CO8B) and attractin], central nerve system-damage-related serum proteins [apolipoprotein D (APOD), alpha-1-antitrypsin, plasma kallikrein and ADAMTS-like protein 3] were observed among three study groups. We furthered demonstrated that site-specific N -glycans on APOD on site 98, CO8B on sites 243 and 553 are potential markers to differentiate MS from NMOSD with an area under receiver operating curve value > 0.75. All these observations indicate that remitting MS or NMOSD patients possess a unique disease-associated glyco-signature in their serum proteins. We conclude that monitoring one's serum protein glycan profile using this high-throughput analysis may provide an additional diagnostic criterion for differentiating diseases, monitoring disease status and estimating response-to-treatment effect.